Scots pine defensins inhibit Ips acuminatus α-amylase activity - Yurii Yusypovych; Oleh Kit; Volodymyr Kramarets; Yuliia Shalovylo; Mykola Korol; Volodymyr Zaika; Hryhoriy Krynytskyy; Valentyna Kovaleva (Біологічні студії, 2023)
Background. Pine bark beetle Ips acuminatus (Gyllenhal, 1827) is one of the most harmful pests of pine trees as it affects the phloem of the upper part of the stem and branches, disrupting the flow of nutrients and water to the crown. I. acuminatus feeds by plant tissues rich in starch, so α-amylases must play a pivotal role in the carbohydrate metabolism of these insects. However, in conifer bark beetles, α-amylases remain poorly understood. Materials and Methods. To detect the α-amylase activity in the digestive system of I. acuminatus, we obtained extracts from larvae, pupae, and adults that were collected from naturally infested Scots pine. The α-amylase activity of crude extracts from different stages and parts of the bark beetle’s body was assessed using 1% starch agar plates. The quantitative evaluation of the α-amylase inhibitory activity of recombinant defensins PsDef1, PsDef2, and PsDef5.1 was performed using the Bernfeld method. The docking models of Scots pine defensins and Ips typographus L. α-amylase (AmyIp) complexes were predicted using the ClusPro 2.0 web server. Results and Discussion. As a result, we found the presence of α-amylase activity in the digestive systems of both larvae and adults of I. acuminatus, but not in pupae. All tested defensins, PsDef1, PsDef2, and PsDef5.1, exhibited inhibitory activity against insect α-amylase at micromolar concentrations. The IC50 values for these peptides were 4.9±0.6 μM, 4.6±0.8 μM, and 2.8±0.5 μM, respectively. In the PsDefs-AmyIt complexes, a network of hydrogen bonds, ionic bridges, and nonbonded contacts are formed between the enzyme and its inhibitor, which prevents the substrate from reaching the catalytic site. The PsDef5.1-AmyIt complex has the largest interfacial contact area, 2328 Å2, in comparison with two other defensins, which correlates well with the inhibitory activity of defensins in this study. Conclusion. Thus, we have identified α-amylase activity in I. acuminatus and demonstrated the ability of Scots pine defensins to inhibit it, suggesting that they play a role in pine defenses against this pest.